E-HAPPY BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN ANAK TUNAGRAHITA - Kholifatul Novita Ningsih, - (2021)
Reading comprehension triggers children to play an active role, not just reading but also understanding, accepting, rejecting and believing what the child has read. The existence of technology that is growing rapidly can be used to develop media according to student learning needs and follow current conditions.The purpose of this study was to develop an E-Happy Book as a learning medium to improve the reading comprehension ability of intellectual disability children according to the needs of students. The development model used is ADDIE consisting of 5 stages (Analysis, Design, Development, Implementation, and Evaluation). The results of the study that e-books are valid for use in the learning process. The results of product testing to students concluded that there was a significant influence and improvement on the subject's reading comprehension ability after the intervention using the E-Happy Book media.E-Happy Book media trial using experimental method with Single Subject Research (SSR) research design A-B-A. The results showed that there was an effect of the E-Happy Book media on increasing the reading comprehension ability of intellectual disability students. Keywords: E-Hapyy Book; Understanding Reading Ability; intellectual disability